2019
DOI: 10.1111/idh.12403
|View full text |Cite
|
Sign up to set email alerts
|

On the association between oral piercings and periodontal conditions—A case series

Abstract: Objective: To investigate the association between oral piercings and periodontal health or inflammation in patients seeking treatment at the University of Basel, Switzerland. Material and methods:Records of patients from the pool of patients at the Department of Periodontology, Endodontology and Cariology were consecutively screened between November 2016 and January 2017. Eighteen patients with a tongue and/or a lip piercing were included. Three out of 18 patients wore both piercings, that is 14 tongue piercin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(37 citation statements)
references
References 29 publications
1
31
1
4
Order By: Relevance
“…The importance of the dental team was evaluated by Maspero C. et al [10] in 2014. Our study confirmed information found in literature [11][12][13][14] describing how oral piercings are the cause of a series of complications, such as dental abrasions, dental fractures, gingival recessions and loss of attachment of periodontal tissues, but also problems related to temporomandibular joint, as stated by Mejersjö in 2016 [15]. It is therefore necessary to establish education programs in schools between dentistry students and dentists themselves, in order to prevent the aforementioned complications reported, respectively, by Silk H et al [16], Junco P et al [17] and McGeary SP et al [18].…”
Section: Discussionsupporting
confidence: 92%
“…The importance of the dental team was evaluated by Maspero C. et al [10] in 2014. Our study confirmed information found in literature [11][12][13][14] describing how oral piercings are the cause of a series of complications, such as dental abrasions, dental fractures, gingival recessions and loss of attachment of periodontal tissues, but also problems related to temporomandibular joint, as stated by Mejersjö in 2016 [15]. It is therefore necessary to establish education programs in schools between dentistry students and dentists themselves, in order to prevent the aforementioned complications reported, respectively, by Silk H et al [16], Junco P et al [17] and McGeary SP et al [18].…”
Section: Discussionsupporting
confidence: 92%
“…Percebe-se que há uma modificação na presença de alterações bucais em pacientes que apresentam algum hábito ou apetrecho prejudicial à saúde bucal e a ausência de tais alterações nos que não fazem seu uso, tendo como exemplo o estudo feito por Schmidt et al (2019) acerca dos piercings orais e o estudo de Sorooshian e Kamarozaman (2018) referente aos aparelhos da moda. Temos também que produtos como as pastas a base de carvão ativado podem tirar a atenção de produtos conhecidos, que realmente levam benefícios à saúde bucal como a pasta de dente convencional contendo flúor, fazendo o paciente substituir sua utilização por um produto de evidência científica ainda inconclusiva (Greenwall et al, 2019).…”
Section: Discussionunclassified
“…Temos também que produtos como as pastas a base de carvão ativado podem tirar a atenção de produtos conhecidos, que realmente levam benefícios à saúde bucal como a pasta de dente convencional contendo flúor, fazendo o paciente substituir sua utilização por um produto de evidência científica ainda inconclusiva (Greenwall et al, 2019). De maneira geral os hábitos e acessórios nocivos influenciados pelas mídias sociais e prejudiciais à saúde bucal abordados podem causar cáries (Alhazmi et al, 2021;Sorooshian & Kamarozaman, 2018;Ziebolz et al, 2019;Covello et al, 2020), progressão da doença periodontal (Junco et al, 2017;Covello et al, 2020;Sorooshian & Kamarozaman, 2018;Ziebolz et al, 2019;Schmidt et al, 2019) e alterações em tecido gengival (Sorooshian & Kamarozaman, 2018;Schmidt et al, 2019;Covello et al, 2020;Junco et al, 2017;King et al, 2018). A alteração em comum encontrada entre os três hábitos/acessórios nocivos estudados (Carvão ativado, Aparelhos da Moda e Piercing oral) foi a influência sob a doença periodontal (Junco et al, 2017;Covello et al, 2020;Sorooshian & Kamarozaman, 2018;Ziebolz et al, 2019;Schmidt et al, 2019;Greenwall et al, 2019).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Likewise, the largest enamel chip is also located on the buccal edge of a mandibular, which is not only facetted, but situated between, and in occlusion with, other facetted teeth. While a number of factors can produce dental chipping and periodontal problems, contemporary clinical literature notes high rates of tooth damage and periodontal issues associated with facial piercings (Hennequin-Hoenderdos, Slot, & Van der Weijden, 2016;Otzel & Birch, 2016;Schmidt, Calderaro, Weiger, & Walter, 2019). If the groove on the buccal roots of the left M 1 is not a taphonomic artifact, it too may relate to gingival irritation caused by facial piercings.…”
Section: Differential Diagnosis Of Dental Wearmentioning
confidence: 99%